Regionální chemoterapie u experimentálního cholangiokarcinomu veprů - Dufek, V; Petrtýl, J (Casopis lekaru ceskych, 1998)
BACKGROUND: Primary cholangiocarcinoma (PCC) accounts for cca 9% of all carcinomas of the liver and biliary system. Its prognosis of always unfavourable and treatment is difficult. METHODS AND RESULTS: In 25 pigs strain BU PCC was induced chemically with the aim to test the action of regional chemotherapy on the tumor tissue. For treatment 5-fluorouracil, 5-fluoro-2-deoxyuridine, mitomycin C and doxorubicin was used either as monotherapy or in combinations. During chemotherapy a significant reduction of the tumour or fibrotization occurred, as compared with animals not receiving treatment. The median of survival was prolonged from 51.3 to 210.3 days. CONCLUSIONS: Regional chemotherapy is a significant constituent of oncological treatment of PCC. Complications of treatment are negligible and the rest for further treatment are encouraging.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bile Duct Neoplasms; Swine; nádory žlučových cest; chemoterapie nádorů pomocí regionální perfúze; prasata; protokoly protinádorové kombinované chemoterapie; žlučové cesty intrahepatální; zvířata; Cholangiocarcinoma; cholangiokarcinom; Bile Ducts, Intrahepatic; Chemotherapy, Cancer, Regional Perfusion; Animals